The Politics of Administrative Law Judge Decision Making at the FCC in Comparative Licensing Cases. (2nd January 2017) - Taratoot, Cole D.
ABSTRACT: The independence given to judges as a means to limit political interference is the same independence that has allowed many judges to insert their own policy preferences into their decision making. Previous studies on administrative law judge (ALJ) decision making have shown that the influence of political preferences in decision making is found even for judges, housed in the federal bureaucracy, who obtain their positions through merit systems, at the National Labor Relations Board (NLRB) (Taratoot and Howard2011 ), the Department of Housing and Urban Development (Seabrook, Wilk, and Lamb2012 ), and the Environmental Protection Agency (Taratoot2014 ). This article continues this examination of ALJ decision making through analyzing comparative licensing cases decided at the Federal Communications Commission (FCC) between 1984 and 1993 to determine whether the influence of political attitudes is present at the FCC. Modeling after the work of Taratoot and Howard (2012), I theorize that FCC decision making is affected by the personal political preferences of the ALJ, legal factors, litigant characteristics, hierarchical controls via higher reviewing bodes, and political controls. Findings demonstrate that unlike at other previously studied agencies, ideological considerations do not play a role in FCC ALJ decision making. ALJs at the FCC are responsive only to the ideological preferences of the Supreme Court. Thus results with regard to FCC ALJ decision making move against previous research in this area.